The Effect of Liquid Meal Replacements on Cardiometabolic Risk Factors in Overweight/Obese Individuals With Type 2 Diabetes: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Noronha, Jarvis C; Nishi, Stephanie K; Braunstein, Catherine R; Khan, Tauseef A; Blanco Mejia, Sonia; Kendall, Cyril W C; Kahleová, Hana; Rahelić, Dario; Salas-Salvadó, Jordi; Leiter, Lawrence A; Sievenpiper, John L (Diabetes care, 2019)
OBJECTIVE: The evidence for liquid meal replacements in diabetes has not been summarized. Our objective was to synthesize the evidence of the effect of liquid meal replacements on cardiometabolic risk factors in overweight/obese individuals with type 2 diabetes. RESEARCH DESIGN AND METHODS: Data sources included MEDLINE, EMBASE, and the Cochrane Library through 10 December 2018. We included randomized trials of ≥2 weeks assessing the effect of liquid meal replacements in weight loss diets compared with traditional weight loss diets on cardiometabolic risk factors in overweight/obese subjects with type 2 diabetes. Two independent reviewers extracted relevant data and assessed risk of bias. Data were pooled using the inverse variance method. The overall certainty of the evidence was evaluated using GRADE (Grading of Recommendations Assessment, Development and Evaluation). RESULTS: Nine trial comparisons (N = 961 [median follow-up 24 weeks]) met eligibility criteria. Mean differences were for body weight -2.37 kg (95% CI -3.30 to -1.44), BMI -0.87 kg/m2 (-1.31 to -0.42), body fat -1.66% (-2.17 to -1.15), waist circumference -2.24 cm (-3.72 to -0.77), HbA1c -0.43% (-0.66 to -0.19) (-4.7 mmol/mol [-7.2 to -2.1]), fasting glucose -0.63 mmol/L (-0.99 to -0.27), fasting insulin -11.83 pmol/L (-23.11 to -0.54), systolic blood pressure -4.97mmHg (-7.32 to -2.62), and diastolic blood pressure -1.98 mmHg (-3.05 to -0.91). There was no effect on blood lipids. The overall certainty of the evidence was low to moderate owing to imprecision and/or inconsistency. CONCLUSIONS: Liquid meal replacements in weight loss diets lead to modest reductions in body weight, BMI, and systolic blood pressure, and reductions of marginal clinical significance in body fat, waist circumference, HbA1c, fasting glucose, fasting insulin, and diastolic blood pressure. More high-quality trials are needed to improve the certainty in our estimates.
Keywords: Meals; Obesity; inzulin; mužské pohlaví; Diabetes Mellitus, Type 2; Insulin; jídla; Adult; Overweight; diabetes mellitus 2. typu; redukční dieta; Fasting; Body Weight; omezení příjmu potravy; Cardiovascular Diseases; ženské pohlaví; Randomized Controlled Trials as Topic; Humans; tělesná hmotnost; obezita; nadváha; rizikové faktory; dospělí; randomizované kontrolované studie jako téma; Diabetic Angiopathies; diabetické angiopatie; Female; Risk Factors; Diet, Reducing; kardiovaskulární nemoci; lidé; Male